2021
DOI: 10.1007/s10943-021-01225-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Affect Balance: Psychological Well-being of Church of England Clergy and Laity During the COVID-19 Pandemic

Abstract: Psychological well-being was assessed by affect balance (a function of negative and positive affect) during the first COVID-19 lockdown in 2020 among 4449 clergy and laity in the Church of England. Better well-being was promoted by preference for feeling over thinking in the psychological type judging process, being older, belonging to the Evangelical wing of the Church, and living in rural areas. Psychological well-being was lowered among people with a general tendency toward neuroticism, among those with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
(30 reference statements)
0
21
0
Order By: Relevance
“…Drawing on data from the Coronavirus, Church & You Survey , Village and Francis (2021b) employed the TIBACh to test the personal, psychological, contextual, and ecclesial correlates of individual differences in psychological well-being among clergy and laity. Data from this analysis, drawing on 4,449 participants, confirmed that personal factors were important (especially age, with older participants reporting a better outcome); psychological factors were important (especially emotional volatility and extraversion, with stable extraverts reporting a better outcome); ecclesial factors were important (especially church orientation, with Anglo-Catholics reporting a worse outcome and Anglican Evangelicals reporting a better outcome compared with Broad Church participants); and contextual factors were important.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on data from the Coronavirus, Church & You Survey , Village and Francis (2021b) employed the TIBACh to test the personal, psychological, contextual, and ecclesial correlates of individual differences in psychological well-being among clergy and laity. Data from this analysis, drawing on 4,449 participants, confirmed that personal factors were important (especially age, with older participants reporting a better outcome); psychological factors were important (especially emotional volatility and extraversion, with stable extraverts reporting a better outcome); ecclesial factors were important (especially church orientation, with Anglo-Catholics reporting a worse outcome and Anglican Evangelicals reporting a better outcome compared with Broad Church participants); and contextual factors were important.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was used was used in relation to psychological wellbeing in a survey during the first lockdown to produce the Index of Balanced Affect Change (TIBACh), which proved a useful tool in measuring change in positive and negative affect since the pandemic began. (Village & Francis, 2021b, 2021c. The same instrument was used in the third lockdown, in 2021, along with items asking about self-perceived changes in spiritual wellbeing and health since the pandemic began.…”
Section: Measuring Change In Spiritual Wellbeing Psychological Wellbe...mentioning
confidence: 99%
“…the caring and worrying for one's own family during the pandemic, or personal factors, e.g. neuroticism, or even location (Village & Francis 2021a). Pastoral burnout in terms of spiritual emptiness often arises if there are conflicts between family life and vocational work-load (Frederick et al 2021).…”
Section: Stress and Spirituality: Intertwined And Work-life-relatedmentioning
confidence: 99%
“…family situation) and place of residence (e.g. city or country), as well as the work context itself (Village & Francis 2021a).…”
Section: Introductionmentioning
confidence: 99%